2021
DOI: 10.3390/crops1020009
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Pretreatment Modulates Wheat Responses to Glyphosate

Abstract: Glyphosate is an extensively used herbicide because of its non-selective action for weed control. Salicylic acid (SA) is a phenolic compound that has the potential to increase plant tolerance to diverse stresses. To test SA ability to modulate plant responses to glyphosate we used young wheat (Triticum aestivum L.) seedlings grown as a water culture. Plants were sprayed with 1 mM SA, and 24 h later with 0.5 mM glyphosate. All measurements were performed 14 days after herbicide treatment. Wheat growth was reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It is believed that this increase is due to oxidative damage induced by glyphosate. Furthermore, Sergiev et al (2020) reported that oxidative damage caused by glyphosate application increased significantly the proline content in pea plants; a similar response was also observed in wheat (Shopova et al, 2021). Rapid accumulation of free proline is a response to oxidative stress, with lines G4 and G3 showing a high positive deviation from the average, which are considered the most tolerant under oxidative stress (figure 2).…”
Section: Proline Content and Soluble Sugars Accumulationmentioning
confidence: 59%
See 1 more Smart Citation
“…It is believed that this increase is due to oxidative damage induced by glyphosate. Furthermore, Sergiev et al (2020) reported that oxidative damage caused by glyphosate application increased significantly the proline content in pea plants; a similar response was also observed in wheat (Shopova et al, 2021). Rapid accumulation of free proline is a response to oxidative stress, with lines G4 and G3 showing a high positive deviation from the average, which are considered the most tolerant under oxidative stress (figure 2).…”
Section: Proline Content and Soluble Sugars Accumulationmentioning
confidence: 59%
“…The maximum increase in MDA was observed in line G5 (65.8 nmol.g -1 FW), followed by line G3 (52.83 nmol.g -1 FW). The significant increase in MDA content indicates a strong imbalance of the biomembrane lipid peroxidation in the herbicide-treated plants (Shopova et al, 2021). However, we recorded a slight increase of MDA content in genotypes Jupare C 2001, Boutaleb, and Oued el bared with 21.09, 26.32, and 26.96 nmol.g -1 FW respectively, with an average of 35.24; genotypes with a lower level of lipid peroxidation are considered more tolerant to oxidative damage.…”
Section: Lipid Peroxidation Assaymentioning
confidence: 99%